Discrete element modelling of uniaxial constant strain rate tests on asphalt mixtures - Cai, W.; McDowell, Glenn R.; Airey, G.D. (Springer Verlag, 2013)
Constant strain rate tests for a graded asphalt mixture under three constant strain rates have been undertaken in the laboratory. The Discrete Element Model has been used to simulate the laboratory tests with a numerical sample preparation procedure being developed to represent the physical specimen. The Burger’s model has been used to represent the time dependent behavior of the asphalt mixture. The Burger’s model was implemented to give bending and torsional resistance as well as in direct tension and compression. The stress-strain response for the laboratory tests and the simulations under three loading speeds were recorded. The results show reasonable agreement when the bond strengths in the model are made to be a function of strain rate. Both normal and Weibull distributions have been used for the bond strengths between the aggregate particles. The effects on the stress-strain response of bond strength variability and particle position are proved to be negligible. Bond breakage was recorded during the simulations to explain the internal damage within the sample. The modified Burger’s model has proved to be a useful tool in modeling the bending and torsional resistance at particle contacts in an asphalt mixture, in order to correctly predict observed behavior.